Peran Kesenian Syarafal Anam Dalam Mencegah Dekadensi Moral Pemuda Desa Pelajau Kecamatan Karang Tinggi Kabupaten Bengkulu Tengah - Gustian Apiko; Qolbi Khoiri; Hamdan Efendi (JPT : Jurnal Pendidikan Tematik, 2025)
The purpose of this study is to find out what Islamic religious education values ​​are contained in the art of syarafal anam in Pelajau village, Karang Tinggi sub-district, Central Bengkulu Regency and how the role of syarafal anam art in preventing moral decadence of the youth of Pelajau village, Karang Tinggi sub-district, Central Bengkulu Regency. The research method used in this study is qualitative, namely a research method based on the philosophy of post-positivism, which is used to research in natural object conditions, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined), data analysis is inductive / qualitative, and the results of qualitative research emphasize meaning rather than generalization. The approach used in this study is descriptive, namely researchers directly go into the field to conduct research. The results of this study are, the art of syarafal anam in Pelajau village is an Islamic art brought by the ancestors and now still exists and is still preserved, in which there are Islamic religious educational values, namely the value of worship, moral values ​​and values ​​of respect. The role of syarafal anam art in preventing the moral decadence of youth in Pelajau village is as a gathering place for youth to do positive things. Because in this art there are many moral values ​​that can be learned and applied in society, especially by the youth themselves.